2016
DOI: 10.31018/jans.v8i2.885
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical investigations on vigour enhancement in aged seeds upon seed priming in onion

Abstract: Loss in seed quality that occurs during all process, from maturation in the field to storage, leads to seed deterioration. Storage of onion seeds under ambient, hot and humid conditions is very problematic since these conditions deteriorate seed quality faster. Seed deterioration is associated with many metabolic defects that occur due to changes in enzymes and protein levels. This deterioration can be rectified to the extent possible by the technique of seed priming. The results clearly indicated that priming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…GA 3 is widely applied to improve the performance of aged seed. Yin et al 2015and Umesha et al (2016) reported that GA 3 priming recovered the germination in artificially aged seeds of Brassica napus and aged onion seeds due to the reactivation of enzyme activities and proteins related to germination. Auxin-priming was found to increase the germination, amount of seminal roots and activities of antioxidant enzymes of deteriorated tall wheatgrass seeds (Eisvand et al 2010).…”
Section: R a F T Discussionmentioning
confidence: 99%
“…GA 3 is widely applied to improve the performance of aged seed. Yin et al 2015and Umesha et al (2016) reported that GA 3 priming recovered the germination in artificially aged seeds of Brassica napus and aged onion seeds due to the reactivation of enzyme activities and proteins related to germination. Auxin-priming was found to increase the germination, amount of seminal roots and activities of antioxidant enzymes of deteriorated tall wheatgrass seeds (Eisvand et al 2010).…”
Section: R a F T Discussionmentioning
confidence: 99%
“…In the present investigation, it was observed that percent improvement in seed quality due to seed priming in old lot (aged seeds) is more as compared to fresh lot (Table 2). Umesha et al, (2016) opined that seed deterioration can be rectified to the extent possible by the technique of seed priming. Their study of biochemical investigations on vigour enhancement in aged seeds upon seed priming in onion clearly indicated that priming would reestablish the lost seed vigour in aged seeds due to reactivation of enzyme activity in old seeds.…”
Section: Effect Of Seed Priming On First Count and Seed Germinationmentioning
confidence: 99%